P.190 Choosing Endovascular Treatment or Thrombolysis in Patients with Pre-stroke Comorbidities: UNMASK EVT, a Worldwide Survey. (November 2021) - Ganesh, A; Kashani, N; Ospel, JM; Wilson, AT; Foss, MM; Saposnik, G; Al-Mekhlafi, MA; Goyal, M; Menon, BK; Hill, MD
Abstract : Background: Decisions to treat large-vessel occlusion with endovascular therapy(EVT) or intravenous alteplase depend on how physicians weigh benefits against risks when considering patients' pre-stroke comorbidities. Methods: In an international survey, experts chose treatment approaches under current resources and under assumed ideal conditions for 10 of 22 randomly assigned case-scenarios. Five included comorbidities(metastatic/non-metastatic cancer, cardiac/respiratory/renal disease, non-disabling/mild cognitive impairment[MCI], physical dependence). We examined scenario/respondent characteristics associated with EVT/alteplase decisions using multivariable logistic regressions. Results: Among 607 physicians(38 countries), EVT was favoured in 1, 097/1, 379(79.6%) responses for comorbidity-related scenarios under current resources versus 1, 510/1, 657(91.1%, OR:0.38, 95%CI.0.31-0.47) for six "level-1A" scenarios (assuming ideal conditions:82.7% vs 95.1%, OR:0.25, 0.19-0.33). However, this was reversed on including all other scenarios(e.g. under current resources:3, 489/4, 691[74.4%], OR:1.34, 1.17-1.54). Responses favouring alteplase for comorbidity-related(e.g.75.0% under current resources) scenarios were comparable to level-1A scenarios(72.2%) and higher than all others(60.4%). No comorbidity-related factor independently diminished EVT-odds. MCI and dependence carried higher alteplase-odds; cancer and cardiac/respiratory/renal disease had lower odds. Relevant respondent characteristics included performing more EVT cases/year (higher EVT, lower alteplase-odds), practicing in East-Asia (higher EVT-odds), and in interventional neuroradiology(lower alteplase-odds vs neurology). Conclusions: Moderate-to-severe comorbidities did not consistently deter experts from EVT, suggesting equipoise about withholding EVT based on comorbidities. However, alteplase was often foregone when respondents chose EVT.